2019
DOI: 10.3390/ma12162643
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bilayer Polycaprolactone Membrane for Guided Bone Regeneration: Combining Electrospinning and Emulsion Templating

Abstract: Guided bone regeneration is a common dental implant treatment where a barrier membrane (BM) is used between epithelial tissue and bone or bone graft to prevent the invasion of the fast-proliferating epithelial cells into the defect site to be able to preserve a space for infiltration of slower-growing bone cells into the periodontal defect site. In this study, a bilayer polycaprolactone (PCL) BM was developed by combining electrospinning and emulsion templating techniques. First, a 250 µm thick polymerised hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 110 publications
5
78
0
Order By: Relevance
“…We showed that murine longbone osteocytes (MLO-A5s) attached, proliferated and infiltrated throughout the interconnects of the PCL PolyHIPE scaffolds. Suitability of the pores for blood vessel ingrowth was also shown using chick chorioallantoic membrane (CAM) assay (Figures 13L-O; Aldemir Dikici et al, 2019a, 2020.…”
Section: Polyhipes For Hard Tementioning
confidence: 79%
See 3 more Smart Citations
“…We showed that murine longbone osteocytes (MLO-A5s) attached, proliferated and infiltrated throughout the interconnects of the PCL PolyHIPE scaffolds. Suitability of the pores for blood vessel ingrowth was also shown using chick chorioallantoic membrane (CAM) assay (Figures 13L-O; Aldemir Dikici et al, 2019a, 2020.…”
Section: Polyhipes For Hard Tementioning
confidence: 79%
“…In the photoinitiator selection process, the critical parameter is that the absorption band of the photoinitiator should overlap with the emission spectrum of the light source ( Eibel et al, 2018 ). 2,4,6-Trimethylbenzoyl phosphine oxide/2-hydroxy-2-methyl propiophenone blend ( Johnson et al, 2015 ; Sherborne et al, 2018 ; Aldemir Dikici et al, 2019a , b ) and phenyl bis(2,4,6−trimethyl benzoyl)−phosphine oxide (BAPO) ( Sears et al, 2016 ) are widely used photoinitiators in photo-polymerisation of HIPEs. Photoinitiators are mostly used in the HIPE composition at a concentration range of 0.2–10% (w/w) of the polymer.…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen membranes derived from animal species are commonly used as resorbable membranes [ 19 ]. Collagen is a major structural protein of extracellular matrix and supports the growth of various tissues, and also has the advantages of inducing little inflammation and of being noncytotoxic [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%